California TRV-based VIGS vectors mediate gene silencing at elevated temperatures but with greater growth stunting - Jamilur Rahman; Ian T. Baldwin; Klaus Gase (BMC Plant Biology, 2021)
Abstract Background Tobacco rattle virus (TRV) based virus-induced gene silencing (VIGS), a widely used functional genomics tool, requires growth temperatures typically lower than those of the plant’s native environment. Enabling VIGS under native conditions in the field according to applicable safety regulations could be a revolutionary advance for ecological research. Results Here, we report the development of an enhanced thermal tolerant VIGS vector system based on a TRV California isolate. cDNA clones representing the whole viral genome were sequenced and used to construct separate binary plant transformation vectors for functional elements of RNA1 (6765 nt) and RNA2 (3682 nt). VIGS of target genes was induced by transient transformation of the host plant with both vectors or by treating the host plant with sap from already VIGS induced plants. In Nicotiana attenuata the silencing efficiency of the PDS (phytoene desaturase) gene was 90% at 28 °C and 78% at 30 °C. Silencing at these temperatures was more prominent and durable than silencing induced by the widely used TRV PpK20-based pBINTRA6/pTV00 system, but was associated with a viral phenotype. Differences in the suppressor protein and RNA dependent RNA polymerase sequences between the TRV California isolate and PpK20 may be the reason for their different thermal tolerance. Conclusions The new TRV California-based VIGS vectors induce gene silencing in Nicotiana attenuata at higher temperatures than the existing pBINTRA6/pTV00 vector system, but cause greater growth defects. The new vector system opens up an avenue to study genes functions in planta under field conditions.